Sistem Pendukung Keputusan Pemilihan Proyeketor Menggungakan Metode Weighted Aggregated Sum Product Assessment - Rini Nuraini (LPPM Universitas Potensi Utama, 2022)
A projector is a device that can project the display from a computer or laptop onto a screen to make it look bigger. Projectors have many benefits including as a presentation tool, as an information medium, entertainment media and so on. How important the function of the projector is that there are many brands or brands of projectors that offer various capabilities and specifications. This becomes a problem because someone sometimes does not have knowledge of the projector specifications that suit their needs. The main objective of this research is to develop a decision support system for selecting projector equipment using the Aggregated Sum Product Assessment (WASPAS) method, in order to obtain the best alternative that suits the needs of several alternatives and certain criteria. The WASPAS method is able to solve multi-criteria problems through optimization of the analysis to get the best alternative. The DSS developed is based on a website, with the main features including managing criteria and weight data, alternative data, conducting alternative assessments, calculating processes using the WASPAS method and displaying the best alternative in the form of ranking. In addition, the developed system produces valid WASPAS method calculations, because the results are in accordance with manual calculations. Based on the test through the black-box testing method, it shows that the developed system has been running well.